Desenvolvimento geográfico desigual e o território da diferença: uma análise socioespacial do bairro Ponta d’Areia, São Luís, Maranhão - Tiers, Thiers Fabrício Santos (2019)
In capitalism, space has become a commodity par excellence, and on a global scale it reproduces unevenly. In this sense, capitalism has in uneven geographical development its base, materializing at different scales and reflecting class society. Having as empirical reference the local scale, more precisely the Ponta d´Areia neighborhood, located in the city of São Luís, Maranhão, presents elements that interact with development, inequality and difference. In this perspective, globalization, capital accumulation, spatial adjustment, consumption and time are categories that permeate the commodity space, which are expressed through gentrification and socio-spatial segregation, in which the issue of housing and the form of consumption illustrates the mentioned neighborhood. The research was based on historical materialism, having as methodological procedures: a) survey and bibliographical analysis on the subject; b) the identification and analysis of social agents; c) conducting 4 field stages in which direct observations, data collection through investigation and interviews with the social agents (residents) involved in the area, as well as the photographic record were carried out; d) tabulation, analysis and interpretation of data and information obtained. The results show that the Ponta d'Areia neighborhood has gradually become one of the most valued in the city of São Luís, but it has numerous aggravating factors that reveal the capitalist socio-spatial contrasts, which are reflected in the different and unequal patterns of development and life. It is concluded that while in Ponta d'Areia there is an overvalued part, with a high standard of housing, consumption and leisure, there is also a part that does not have access to the infrastructure and the benefits that would complement their housing, coexistence and insertion, which serves as an example of urban sociospatial inequality derived from the logic of capital